The interrelationship between inflammatory cytokines and skeletal muscle decay from the viewpoint of circadian rhythms. (2nd November 2022) - Luo, Xuguang; Yang, Xinhua; Yang, Yanping; Li, Hairong; Cui, Huilin; Cao, Ximei
Abstract: Circadian rhythms affect a variety of physiological processes. Disruption of circadian rhythms causes many diseases, most of which are associated with inflammation. Disruption of circadian rhythms has a detrimental impact on the function of immune system. It is common to find that circulatory LPS are increased. LPS induces immune cells to produce inflammatory cytokines. Inflammatory cytokines play a role in skeletal muscle decay. Rev-erbβ has been identified as a critical regulator of circadian rhythms and a factor in inflammation. Another effect of disruption is a concomitant disturbance of glucose–insulin metabolism, which skeletal muscle likely contributes to considering it is a key metabolic tissue. Disruption of circadian rhythms is also related to obesity. Obesity can cause an increase expression of inflammatory cytokines. Maybe obesity with skeletal muscle decay is one of major characteristics. Future studies are needed to obtain a comprehensive understanding of inflammatory cytokines and skeletal muscle decay from the viewpoint of circadian rhythms.